Students’ academic performance and soft skills on graduate employability among students in Universiti Malaysia Sabah - Qhatrunnada Suyansah; Darmesah Gabda; Esther Jawing; Kamsilawati Kamlun; Rose Patsy Tibok; Hiew Wendy; Wirawati Ngui Yi Xe (American Institute of Physics Inc., 2023)
Students' academic success has always been the top priority and is believed to be one of the factors that will help in increasing students' employability. Soft skills are also known to be vital before entering the working world. There have been many studies that sought to investigate factors that influence graduate employability. This study aims to determine the impact of academic factors and soft skills on students' employability after they have graduated from university from two main sources, which are the Feedback on the Attributes of UMS Trainee Who Are Currently Undergoing Industrial Training for the year 2017 and the Graduates Tracer Study 2017 administered by the Ministry of Higher Education Malaysia. The population of the study is all the graduates in the year 2017 and a sample of 1028 students was obtained from the respondents that responded to the two matched main sources. Several tests such as the Chi Square test, Independent T-test, and Mann Whitney U test were employed for analyses to determine the relationships and differences between academic factors and soft skills towards graduate employability. The results show that there are no relationships between academic factors, qualification, and program of study. There seem to be a mean difference between academic factors, such as entry and final CGPA, PPIB results and SPM English results towards employability status of graduates. However, as for soft skills (i.e. knowledge, technical skills, ICT skills, problem solving, communication skills, teamwork, leadership, professionalism and ethics), the results show that only ICT skill is statistically significant towards graduate employability